Digitalization – competence and its connections (Academic Journal of Internal Affairs, 2023)
Aim: The author intends to present in his study the impact appeared – on organizations and individuals – in connection with the emergence of the digital world. He considers it important to show the interconnectedness of the triad of the environment, the organization and the individual.Methodology: In the study, the need to change the examined topic is presented through the definition of concepts related to managerial competence, using a wide range of research methodologies.Findings: Through the description of the general main competencies, it illustrates the development of digital competence, its development, as well as the changes in leadership competencies that are of paramount importance for the future of the organization.Value: The author in this study draws managers' attention to the fact that the sustainability and competitive advantage of today's organizations depends on their ability to adapt to the conditions dictated by the changing environment.
Keywords: organization; digitalization; competence; digital competence